Pengaruh Terpaan Iklan Media Sosial Terhadap Minat Beli Produk Scarlett Whitening Pada Mahasiswa FEB Universitas Islam Malang - Alya Nurul Sa’diyah; Eka Farida; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of exposure to social media advertising, video marketing content, product posters, and celebrity endorsements on interest in buying Scarlett Whitening products in FEB students, Islamic University of Malang. This study uses a quantitative approach with explanatory research methods. The data used is primary data, the data collection method uses a questionnaire via Google form. The technique of determining the sample using random sampling of 95 respondents with a system of determining the number of samples using the formula by Malhotra.The results of this study indicate that there is a significant effect on the video content marketing variable on buying interest. While the product poster and celebrity endorse variables showed no significant effect on buying interest in Scarlett Whitening products. 37.5% buying interest is influenced by the variables in this study, while 62.5% buying interest is influenced by other variables not included in this study. Keywords: Advertising, buying interest, marketing content, product posters, celebrity endorsements, scarlett whitening